Ibuyambo: reconnecting rural Xhosa people with the natural environment in the contemporary time - Sihlahla, Athenkosi (School of Architecture, Planning and Geomatics, 2021)
In the history of rural Xhosa people lies a rich connection between the people and the natural environment. Access to the natural environment provided a sense of wellbeing, a link to ancestral spirits, a location for religious rituals and a wealth of culturally inspired uses within the landscape. This connection underlies certain cultural activities and functions such as religious and traditional rituals, fuel wood collection, water collection, and farming. However, this incredible connection is under threat due to urbanization, environmental conservation strategies, Betterment planning and the introduction of new developments. Betterment planning appears to be the major cause of the isolation of rural Xhosa people from the natural environment. This study investigates how Betterment planning (a conservation scheme that was implemented in the 1930's, aiming at improving rural black people's lives), impacted the rural Xhosa people's social and cultural relationship with the natural environment. The study draws attention to how people lived before Betterment planning, in relation to how people are living now. The aim of the project is to generate a design that will improve contemporary rural Xhosa people's lives, while reconnecting them with the natural environment. The design focuses on interventions that may facilitate the strengthening of rural Xhosa peoples social and cultural ties to the natural environment as well as to revive land production, land use and appreciation of cultural ecosystem services. The overall concept of the design derives from a historically familiar Xhosa homestead layout and the relationship of its domestic spaces. The case study of this project is Shixini village, Willowvale.